2018
DOI: 10.1186/s40425-018-0356-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the TGFβ pathway with galunisertib, a TGFβRI small molecule inhibitor, promotes anti-tumor immunity leading to durable, complete responses, as monotherapy and in combination with checkpoint blockade

Abstract: BackgroundTGFβ signaling plays a pleotropic role in tumor biology, promoting tumor proliferation, invasion and metastasis, and escape from immune surveillance. Inhibiting TGFβ’s immune suppressive effects has become of particular interest as a way to increase the benefit of cancer immunotherapy. Here we utilized preclinical models to explore the impact of the clinical stage TGFβ pathway inhibitor, galunisertib, on anti-tumor immunity at clinically relevant doses.ResultsIn vitro treatment with galunisertib reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
210
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(225 citation statements)
references
References 55 publications
(73 reference statements)
6
210
0
Order By: Relevance
“…In addition, concomitant TGFb/PD-L1 pathway inhibition greatly enhanced T-cell responses in esophageal squamous cell carcinoma (21), and blockade of greatly sensitized genetically reconstituted models of colon cancer metastasis (22). Further, TGFb pathway inhibitors enhanced responsiveness to PD-1/PD-L1-neutralizing antibodies in mice bearing poorly immunogenic 4T1-LP breast tumors (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, concomitant TGFb/PD-L1 pathway inhibition greatly enhanced T-cell responses in esophageal squamous cell carcinoma (21), and blockade of greatly sensitized genetically reconstituted models of colon cancer metastasis (22). Further, TGFb pathway inhibitors enhanced responsiveness to PD-1/PD-L1-neutralizing antibodies in mice bearing poorly immunogenic 4T1-LP breast tumors (23).…”
Section: Discussionmentioning
confidence: 99%
“…3B). 20 Murine colon carcinoma and breast cancer models further illustrated that M7824 attenuates tumor burden and enhances OS compared with TGF-β blockade alone, as evidenced by elevated CD8-positive T-cell and NK cell activation. This result supports a study illustrating that TGF-β signaling diminishes tumor response to PD-1/PD-L1 blockade by excluding CD8-positive effector T cells from the tumor parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Although these Cancer October 15, 2019 clinical trials still are ongoing and treatment outcome remains unclear, preclinical studies have demonstrated that galunisertib can increase anti-PD-L1 monotherapyelicited intratumor immune-associated gene expression. 20 Murine colon carcinoma and breast cancer models further illustrated that M7824 attenuates tumor burden and enhances OS compared with TGF-β blockade alone, as evidenced by elevated CD8-positive T-cell and NK cell activation. 21 In the current study, we did not observe any obvious correlation between PD-L1-positive tumors and response to PD-1/PD-L1 blockade, 4,13 yet early results have suggested that PD-L1 expression in immune and tumor cells was associated with response to pembrolizumab in a subset of patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…It illustrates an unpredicted immune regulatory mechanism that inhibits the development of antitumor immunity and may diminish the effect of immunotherapy [47]. In agreement with the idea of microenvironment, targeting the TGF-β pathway with a TGFβRI small molecule inhibitor (galunisertib) has been proven to support anti-tumor immunity in a solid tumor study [48]. The treatment with galunisertib showed strong dose-dependence with anti-tumor activities where T cell proliferation mediated by TGF-β was suppressed.…”
Section: Discussionmentioning
confidence: 57%